Pharmacoeconomic Analysis of Alcohol-Dependent Patients Drug Therapy - Vaskova, Larisa B; Maksimkina, Elena A; Arabyan, Manuk A (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Methodologic approach to the pharmacoeconomic evaluation of the drug therapy for alcoholdependent patients in an inpatient facility in real clinical practice was proposed by the authors. The aim of the study was to perform a pharmacoeconomic analysis of the disease treatment cost in alcohol-dependent patients according to their primary diagnosis in an inpatient facility.During the period from 2015 to 2016, the authors analyzed 120 medical histories of patients with primary diagnosis F.10.2 (Alcohol dependence) – disease-related group (DRG) №1 and F.10.3 (Alcohol withdrawal syndrome) – DRG №2. In total, in 2015 there were 27 drugs from 15 PT groups indicated and in 2016 – 36 drugs from 16 PT groups. It was established that in 2015 the main budget share was spent on PTG antiepileptics and vitamins (68.14 USD or 21.24% and 59.23 USD or 18.46% of the total sun, respectively), and in 2016 - on PTG anxiolytics and antidepressants (99.41 USD or 16.67%). Dhaka Univ. J. Pharm. Sci. 18(1): 39-42, 2019 (June)